Comparable efficacy and safety of dimethyl fumarate and teriflunomide treatment in Relapsing-Remitting Multiple Sclerosis: an Italian real-word multicenter experience - D’Amico, Emanuele (Ther Adv Neurol Disord, 2018)
BACKGROUND: The aim of the study was to evaluate the achievement of ‘no evidence of disease activity’ (NEDA) over a 12-month period in a large multicenter population with relapsing remitting multiple sclerosis (RRMS) treated with delayed-release dimethyl fumarate (DMF) and teriflunomide (TRF) using a propensity-score adjustment. METHODS: A time-to-event method was used to determine the percentages of patients with RRMS (pwRRMS) in both groups achieving NEDA 3 (no relapses, no 12-week confirmed disability progression, and no new T2/gadolinium-enhancing brain lesions). We described the safety profile of the investigated drugs. RESULTS: Of the 587 pwRRMS treated with DMF and the 316 pwRRMS treated with TRF, 468 pwRRMS were successfully paired by propensity score: 234 on DMF and 234 on TRF. The percentages of pwRRMS who achieved NEDA 3 were 80.3% in the DMF group and 77.2% in the TRF group. Serious adverse events occurred in four (1.9%) pwRRMS on DMF and in three (1.3%) pwRRMS on TRF. CONCLUSIONS: DMF and TRF significantly impacted RRMS disease activity in our study. Serious safety concerns were recorded in less than 2% of the studied population.